1998
DOI: 10.1507/endocrj.45.315
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutation (C1263R) in the Thyroglobulin Gene Causes Congenital Goiter with Mild Hypothyroidism by Impaired Intracellular Transport.

Abstract: Abstract.Metabolic abnormalities in thyroid hormonogenesis cause congenital goiter. Here we studied a case of mild hypothyroidism caused by a novel missense mutation in the thyroglobulin (TG) gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
3
23
0
1
Order By: Relevance
“…These findings are consistent with those observed in a case of defective intracellular transport of Tg (Fig. 2B) (14).…”
Section: Morphological and Biochemical Analysis Of The Thyroid Of Patsupporting
confidence: 93%
“…These findings are consistent with those observed in a case of defective intracellular transport of Tg (Fig. 2B) (14).…”
Section: Morphological and Biochemical Analysis Of The Thyroid Of Patsupporting
confidence: 93%
“…Histological studies pointed to abnormal protein trafficking from endoplasmic reticulum to Golgi, which is a frequent consequence of Tg gene mutations (14). We have shown that Tg mutations, C1245R and C1977S, which perturb correct folding of Tg protein, caused impaired intracellular transport, leading to accumulation of abnormal Tg in endoplasmic reticulum (9,15,16). The mutation C1058R also caused defects in intracellular transport as shown by carbohydrate analysis of Tg protein and increased expression of molecular chaperones in the patients' thyroid (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…One of these patients was euthyroid, the other individual had mild hypothyroidism, but both had undetectable TG levels. As demonstrated by sensitivity to digestion with endoglycosidase H and formation of high molecular aggregates, this mutation is retained in the ER (84,85).…”
Section: Tg Gene Mutations In Humansmentioning
confidence: 95%
“…Two unrelated patients with congenital goiter were found to be homozygous for a point mutation (c.3790T>C; originally described as c.3787T>C) leading to substitution of cysteine 1264 in the precursor by arginine (84,85). One of these patients was euthyroid, the other individual had mild hypothyroidism, but both had undetectable TG levels.…”
Section: Tg Gene Mutations In Humansmentioning
confidence: 99%